Effectiveness of eHealth interventions for cancer‐related pain, fatigue, and sleep disorders in cancer survivors: A systematic review and meta‐analysis of randomized controlled trials. Issue 2 (17th November 2021) - Li, Juejin; Zhu, Chuanmei; Liu, Chunhua; Su, Yonglin; Peng, Xingchen; Hu, Xiaolin
Abstract: Purpose: To systematically evaluate the effects of Electronic health (eHealth) interventions on fatigue, pain, and sleep disorders in cancer survivors. Design: A systematic review and meta‐analysis was conducted. Methods: Relevant studies were searched from five databases (MEDLINE, Embase, the Cochrane Central Register of Controlled trials, CINAHL, and PsycINFO). The comprehensive literature search was done in December 2020. Only randomized controlled trials (RCTs) that examined the effects of eHealth interventions among cancer survivors were included. Findings: Twenty‐five RCTs were included. The meta‐analysis showed that eHealth interventions had a positive impact on pain interference (SMD = −0.37, 95% CI: −0.54 to −0.20, p  = 0.0001) and sleep disorders (SMD = −0.43, 95% CI: −0.77 to −0.08, p  = 0.02) but not on pain severity or fatigue in cancer survivors. The sensitivity and subgroup analyses indicated that the pooled results were robust and reliable. Conclusion: eHealth interventions are effective in improving pain interference and sleep disorders in cancer survivors. Additional high‐quality RCTs are needed to test the effectiveness of eHealth interventions on fatigue, pain, and sleep disorders in cancer survivors. Clinical relevance: This systematic review and meta‐analysis provides evidence to offer effective and sustainable eHealth care for symptom management among cancer survivors.